The Maguindanaon kulintang musical innovation, transformation and the concept of Binalig - Benitez, Kristina (2005)
This is a study on the music of the Maguindanaon kulintang, a row of eight small pot gongs laid out horizontally. It explores a new way of understanding creativity, innovation, and transformation in Maguindanaon kulintang music. It examines Maguindanaon categories and terms relating to performance practice and puts forth the concept of binalig, and its meaning "made different", as key to explaining musical continuity and change in the kulintang.